Indolamine 2, 3-dioxygenase expression by monocytes and dendritic cell populations in hepatitis C patients. (15th May 2015) - Schulz, S; Landi, A; Garg, R; Wilson, J A; van Drunen Littel-van den Hurk, S
Summary: Dendritic cells (DCs) play an important role in the induction of the primary immune response to infection. DCs may express the tryptophan-catabolizing enzyme indolamine2, 3-dioxygenase (IDO), which is an inducer of immune tolerance. Because there is evidence that chronic hepatitis C virus (HCV) infection leads to functional impairment of certain DC populations, we analysed IDO expression in DCs and monocytes from chronically infected and recovered HCV patients. The IDO1 and -2 expression was increased significantly in the monocytes of chronic HCV patients but, interestingly, not in those from recovered patients. The myeloid DCs from chronically infected HCV patients also showed enhanced IDO1 expression, while no change in either IDO1 or -2 was found for plasmacytoid DCs. Up-regulation of IDO1 gene expression was confirmed by the presence of enhanced kynurenine/tryptophan ratios in the plasma from chronic HCV patients. Increased IDO1 and -2 expression was also observed in monocytes from healthy donors infected with an adapted mutant of the HCV JFH-1 strain ex vivo, confirming a direct effect of HCV infection. These changes in IDO expression could be prevented by treatment with the IDO inhibitor 1-methyl tryptophan (1-mT). Furthermore, maturation of monocyte-derived DCs from chronically infected HCV patients, as well as well as monocyte-derived DCs infected ex vivo with HCV, was impaired, but this was reversed by 1-mT treatment. This suggests that IDO inhibitors may be used to treat chronic HCV patients in vivo, in conjunction with current therapies, or to activate DCs from patients ex vivo, such that they can be administered back as a DC-based therapeutic vaccine.